'Except God, no substance can be conceived': Spinoza on other substances. (8th February 2022) - Noorloos, Ruben
Abstract: This paper argues that Spinoza held substances other than God to be inconceivable. It uses this claim to develop a novel response to the Problem of Other Substances (Garrett 1979, Barry 2019 ), the problem of explaining why some of Spinoza's proofs for God's existence cannot be used to prove the existence of a non-divine substance instead.